(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Globally, Abattoirs produce a considerable amount of byproducts from animals. Although these byproducts are a valuable source of industrial proteins which could be used for a variety of value-added applications, they are currently either underutilized in high-value applications or used in the production of relatively low-value products such as pet food and animal feed . In addition, some byproducts of animal slaughter do not fit in the food and feed chains, thus making their disposal in the environmental a major concern. Waste processing is revolutionized, thus, use of Abattoir waste can be incorporated into the industrial processes with the aim of producing value-added bio-based products such as biogas, biofertilizers, biosurfactants, bioethanol, enzymes and single cell proteins, to name a few. Energy transition through waste to energy pathways leading to biogas production and electricity will help mitigate greenhouse gas emissions. Furthermore, byproducts from abattoir effluents could be used to make high-value items such as animal feed, glue, and fertilizers. The current study evaluated biodegradation of abattoir waste for value added product production under related critical topics such as abattoir waste composition, abattoir waste treatment, and strategies involved with an emphasis on bioremediation/biodegradation and biodegradation’s implications for bioproduct formation. The study infers that a sustainable transition of energy and a cleaner environment lies in conversion of Abattoirs waste to wealth.